Long-term cost-effectiveness analysis of endovascular versus open repair for abdominal aortic aneurysm based on four randomized clinical trials. Issue 6 (24th March 2014) - Epstein, D; Sculpher, M J; Powell, J T; Thompson, S G; Brown, L C; Greenhalgh, R M
Abstract: Background: A number of published economic evaluations of elective endovascular aneurysm repair (EVAR) versus open repair for abdominal aortic aneurysm (AAA) have come to differing conclusions about whether EVAR is cost-effective. This paper reviews the current evidence base and presents up-to-date cost-effectiveness analyses in the light of results of four randomized clinical trials: EVAR-1, DREAM, OVER and ACE. Methods: Markov models were used to estimate lifetime costs from a UK perspective and quality-adjusted life-years (QALYs) based on the results of each of the four trials. The outcomes included in the model were: procedure costs, surveillance costs, reintervention costs, health-related quality of life, aneurysm-related mortality and other-cause mortality. Alternative scenarios about complications, reinterventions and deaths beyond the trial were explored. Results: Models based on the results of the EVAR-1, DREAM or ACE trials did not find EVAR to be cost-effective at thresholds used in the UK (up to £30 000 per QALY). EVAR seemed cost-effective according to models based on the OVER trial. These results seemed robust to alternative model scenarios about events beyond the trial intervals. Conclusion: These analyses did not find that EVAR is cost-effective compared with open repair in the long term in trials conducted in European centres. EVAR did appear to be cost-effective based on the OVER trial, conducted in the USA. Caution must be exercised when transferring the results of economic evaluations from one country to another. Abstract : Not cost-effective in Europe